2003
DOI: 10.1080/0042098032000116086
|View full text |Cite
|
Sign up to set email alerts
|

Does Tax Increment Financing Raise Urban Industrial Property Values?

Abstract: The paper examines the impact of tax increment financing (TIF) on the value of industrial properties in Chicago. Because TIF designation may be self-selected, a two stage procedure is used to estimate the influence of TIF. The authors find that the value of industrial parcels located in mixed-use TIF districts (i.e. those that also contain commercial or residential properties) is higher than that of similar parcels that are not located in a TIF district. However, the value of industrial parcels that are locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 25 publications
1
71
2
Order By: Relevance
“…Finally, Weber et al (2003), analyzed the industrial real estate market in Chicago and reported no evidence of higher industrial property values in TIF neighborhoods when compared to neighborhoods that did have TIFs. The lack of higher prices in TIF districts is not surprising given the first premise of TIF designation in the state of Illinois is the area must suffer from some level of blight.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, Weber et al (2003), analyzed the industrial real estate market in Chicago and reported no evidence of higher industrial property values in TIF neighborhoods when compared to neighborhoods that did have TIFs. The lack of higher prices in TIF districts is not surprising given the first premise of TIF designation in the state of Illinois is the area must suffer from some level of blight.…”
Section: Introductionmentioning
confidence: 97%
“…Tax increment financing (TIF) is one of the predominant economic development policies utilized by municipalities in the United States for fostering market-based urban renewal (Man, 2001;Weber et al, 2003). Originating in California in 1952, TIF has been accepted by 49 states and the District of Columbia (excludes Arizona) and is employed extensively in California, Colorado, Florida, Illinois, Indiana, Minnesota, and Wisconsin.…”
Section: Introductionmentioning
confidence: 99%
“…This comparison is necessary because public officials might be tempted to implement TIF districts around properties expected to appreciate in value regardless of the incentives provided by TIF policy (Weber, Bhatta, and Merriman 2003). Tax increment financing implementation might be endogenously determined.…”
Section: Model Estimationmentioning
confidence: 99%
“…This transformation makes it less likely that the location of a property in the city's downtown area will be correlated with the property's value. 11 Similar to the approach of Weber, Bhatta, and Merriman (2003), the unobserved preference of the city to include a parcel i within a TIF district is expressed as…”
Section: Model Estimationmentioning
confidence: 99%
“…Another group of studies considers the impact of tax-increment financing districts (Byrne, 2010;Dye & Merriman, 1999;Mason & Thomas, 2010;Merriman, Skidmore, & Kashian, 2007Weber, Bhatta, & Merriman, 2003). Under this incentive policy, local governments divert increments to normal property-tax revenue (or other tax revenue), within a designated district, to support services, infrastructure improvements, or tax breaks to businesses in the designated district.…”
Section: Previous Research Literature On Economic Development Incentivesmentioning
confidence: 99%